Analysis of Factors Associated with Prevention of Hiv&Aids Transmission Behavior in Men with Male Sex (MSM) in Indonesia in 2019 - Noer Fatonah Fatonah; Dwi Handayani (Universitas Widya Gama Mahakam Samarinda, 2022)
Background: Male Sex Men (MSM) are one of the high-risk groups for contracting HIV&AIDS due to anal and oral sexual behavior. Based on SIHA 2019 data, MSM is the highest risk factor for HIV and AIDS cases (19%). Research Metodes: The purpose of this study was to identify behavior factors that prevent HIV and AIDS infection in Male Sex Men in Indonesia (MSM). Results: This type of This type of research is non reactive with an ecological study research design with a cross sectional approach. The population in this study is the entire area that became the 2018-2019 IBBS survey consisting of 24 regencies/cities in Indonesia using the specified total population sample. The data obtained were analyzed using univariate and bivariate analysis. Conclusion: The conclusion in this study is there is a strong relationship between predisposing factors (age and knowledge), and driving factors (peer support) with the behavior of preventing HIV&AIDS transmission among MSM in Indonesia